FERDINAN DE SAUSSURE'S SEMIOTIC ANALYSIS ON THE SONG "LELAK LOCE RENDA" - Yosefina Elsiana Suhartini; Thomas Tahir; Clemenstinus Malis; Yohanes Tresno Kurnianto (Lantern: Journal of Language and Literature, 2024)
This research uses Ferdinand de Saussure's semiotic approach to analyze the meaning in the lyrics of the song "Lelak Loce Renda" in the context of Manggarai culture. Descriptive qualitative method was used to translate the song lyrics into Indonesian and English, and to analyze the song lyrics with a personal view. The results of the analysis show that this song contains messages about determination to achieve goals, hard work, advice from parents, and diligent prayer and hope in God. The lyrics reflect a deep meaning and are full of motivational messages, and encourage young people to have strong determination, work hard, and pray in achieving their goals. This research is important to provide a deeper understanding of the meaning of the song "Lelak Loce Renda" and can help in preserving Manggarai folk songs and Manggarai musical traditions